Water productivity using furrow and drip irrigation in hybrid maize - Conde, José; Castillo, Sara; Rivera, Leonor; Gálvez, Paola (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
Agriculture is the economic sector that consumes around 70 % of the total water extracted globally, considering itself a victim of its own inefficiency. The present work was oriented to look for irrigation alternatives that allow a greater productivity of water. The trial was carried out at the Faculty of Agricultural Sciences, Technical University of Machala, Ecuador. The amount of water applied to the corn crop through furrow and drip irrigation was evaluated. The treatments were: furrow irrigation, superficial drip irrigation and subsurface drip irrigation at 20 cm. The trial had a surface area of 450 m2, in a completely randomized block experimental design with three treatments and three repetitions. The control of the irrigation regime was carried out through tensiometers installed for each treatment. The volume of water applied and the dry grain yield in irrigation by furrows was 3,484 m3.ha-1 and 9,175 kg.ha-1, for surface drip irrigation of 1,452 m3.ha-1 and 10,200 kg.ha-1, and for subsurface drip irrigation it was 1,237 m3.ha-1 and 10,181.2 kg.ha-1. The water productivity for the furrow irrigation treatment was 2.63 kg.m-3, for surface drip irrigation it was 7.02 kg.m-3 and for subsurface drip irrigation at 20 cm it was 8.23 kg.m-3 being the highest productivity.